(untitled) (UUM Journal of Legal Studies, 2023)
The rapid emergence and growth of e-commerce have caused an increase in halal issues, especially with the false description of Halal in E-Commerce amongst the various online platform providers. More specifically, halal issues that need legal attention include safety issues, deceptive conduct, misleading representation, and false description. This study aims to analyse the adequacy of the Consumer Protection Act 1999 to protect consumers, especially regarding false descriptions of halal in online transactions. To achieve this objective, the approach is to adopt a qualitative research method, in which content analysis is made by comparing the consumer protection laws in force in other countries. The findings of this study revealed several challenges in applying such laws, which used ambiguous terminologies and imposed limited liabilities on online market operators. A few recommendations have been put forward, such as the interpretation of terms such as ‘consumer,’ ‘goods,’ ‘description,’ and ‘suppliers’ needs. These terminologies have to be revised, in addition to extend the liabilities of online market operators so that there will be better consumer protection for Muslims when they shop online.